Markets as mirrors - Pardo-Guerra, Juan Pablo (Tempo Social, 2017)
This paper queries the conventional conceptualization of markets as networks, institutions, and performative realizations by presenting them as cultural mirrors that reflect the quirks and modes of social organization of their environments. Extending the Weberian metaphor of markets as communities, and combining these with recent anthropological theories of kinship, the paper argues for understanding market processes as sites for the production of social relations rather than merely impersonal transactions. Using discussions of settlement and trading in contemporary financial markets as an example, the article advocates rethinking the role and ontology of markets in modern life.